Time Management And Self-Directed Learning As Predictors Of Academic Performance Of Students In Mathematics - WILLIAM JR. GANZON; MA. MELANIE EDIG (Journal of Social, Humanity, and Education, 2022)
Purpose: This study determined the influence of time management and self-directed learning on the academic performance of students in Mathematics. Methodology: A quantitative research design utilizing descriptive and correlational approaches was employed. 152 Grade 9 respondents were chosen from private schools in Davao City. Results: The findings indicated that time management is manifested most of the time and self-directed learning is much observed. Moreover, the academic performance in Mathematics is not proficient. Further, time management and self-directed learning were found to have no significant relationship with academic performance in Mathematics. Thus, time management and self-directed learning do not significantly predict academic performance in Mathematics. Limitations: This study only highlighted 152 students and 4 private schools that were offering blended learning modality. Contribution: The results and findings of this study can be used as a basis for creating interventions and programs to address problems in academic performance in Mathematics. Novelty: Most previous studies were conducted in a face-to-face learning modality; however, this study is contextualized in the blending learning modality.